Anti-TNF-Mediated Modulation of Prohepcidin Improves Iron Availability in Inflammatory Bowel Disease, in an IL-6-Mediated Fashion. (16th January 2017) - Cavallaro, Flaminia; Duca, Lorena; Pisani, Laura Francesca; Rigolini, Roberta; Spina, Luisa; Tontini, Gian Eugenio; Munizio, Nadia; Costa, Elena; Cappellini, Maria Domenica; Vecchi, Maurizio; Pastorelli, Luca
Abstract : Background. Anaemia is common in inflammatory bowel disease (IBD), frequently resulting from a combination of iron deficiency and of anaemia of chronic disease (ACD). ACD is characterized by macrophage iron retention induced by proinflammatory cytokines. Hepcidin is the master inducer of iron accumulation during ACD, and its production is mainly regulated by IL-6 and the novel erythroid hormone erythroferrone (ERFE). This study evaluates whether anti-TNF monoclonal antibodies therapy modurates hepcidin production and the levels of its main regulators, leading to a restoration of iron homeostasis. Methods. Sera were collected from 21 IBD patients, before each anti-TNF administration, for the first 6 weeks of therapy. Prohepcidin, erythropoietin, erythroferrone, C reactive protein, interleukin-6, iron markers, and haemoglobin levels were measured and clinical activity indexes were evaluated. Results. Serum prohepcidin, IL-6, CRP, and ferritin were significantly reduced after 6-week treatment; an increase in serum iron and total transferrin was observed. No changes in the EPO-ERFE axis were found. Remarkably, haemoglobin was significantly increased. Conclusions. Anti-TNF therapy improves iron metabolism and, subsequently, anaemia in IBD. This effect appears to be related to the modulation of the cytokine network and specifically IL-6 leading to a relevant decrease of hepcidin, a master regulator of ACD.